2022
DOI: 10.1163/22131035-11010008
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights Implications of Stroke Biobanking and Genomics Research in Sub-Saharan Africa

Abstract: Stroke is a major cause of death in Sub-Saharan Africa (ssa) and genetic factors appear to play a part in its pathogenesis. This led to the development of stroke biobanking and genomics research in ssa. Existing stroke studies have focused on causes, incidence rates, fatalities and effects. However, scant attention has been paid to the legal issues about stroke biobanking and genomics research in the sub-region. Therefore, this article examines the legal implications of stroke biobanking and genomics research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…140 Genetic factors and differing disease profiles, including HIV and tuberculosis, are potential contributors to the early onset of stroke in SSA. [141][142][143] Additionally, The Southern African Stroke Prevention Initiative reports a stark awareness gap about the increased risk of stroke for people with hypertension. 144 Moreover, little is known about the relationship between HDP and stroke in SSA, necessitating further research.…”
Section: Current Researchmentioning
confidence: 99%
“…140 Genetic factors and differing disease profiles, including HIV and tuberculosis, are potential contributors to the early onset of stroke in SSA. [141][142][143] Additionally, The Southern African Stroke Prevention Initiative reports a stark awareness gap about the increased risk of stroke for people with hypertension. 144 Moreover, little is known about the relationship between HDP and stroke in SSA, necessitating further research.…”
Section: Current Researchmentioning
confidence: 99%
“…[204][205][206][207] In Africa, the Ibadan Brain Ageing, Dementia And Neurodegeneration (IBADAN) brain bank and the African Neurobiobank ELSI Project 205,208 have demonstrated that 19% to 27% of older Africans are willing to donate brains for research and have also drawn attention to the necessity of paying attention to the legal issues related to biobanking in a unique African context. 206,209,210 The Biobank for Aging Studies (BAS) in Sao Paulo, Brazil 204 has shown that 22% of cases with a Clinical Dementia Rating (CDR) score of zero met the criteria for a neuropathological disease diagnosis, with AD being the most common. 21 It has also been shown that VaD and cerebral small vessel disease are higher in Brazil than in other clinicopathological studies.…”
Section: Biobanksmentioning
confidence: 99%
“…(Willis, 2023) reveals that human rights are only part of the most fundamental human right to life. (Adigun et al, 2022) argues that human rights are rights that have been established by national and international legal systems. (Natamiharja et al, 2022) an effort to maintain the security of human existence as a whole through actions that balance the interests of individuals with the common interest.…”
Section: Introductionmentioning
confidence: 99%